2018
DOI: 10.1097/brs.0000000000002602
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Surgical Decompression in Patients With Very Severe Degenerative Cervical Myelopathy

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
4
11
0
Order By: Relevance
“…In our series, we had an improvement in the mJOA score from 13.9 to 16.5. This is in accordance to other main series [15,16,23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our series, we had an improvement in the mJOA score from 13.9 to 16.5. This is in accordance to other main series [15,16,23].…”
Section: Discussionsupporting
confidence: 93%
“…Our results confirm recent series [6,7,10,11,12,13,14,15,16] in which the anterior approach for the treatment of more than four levels (cervical) is safe and effective in the treatment of multilevel cervical degenerative myelopathy and radiculopathy, in addition to multilevel cervical spondylodiscitis, complex traumatic cervical fractures, metastatic cervical spine tumor, and ossification of the posterior longitudinal ligament.…”
Section: Discussionsupporting
confidence: 89%
“…After surgery, the functional outcome indicated by the mJOA-LEF and Nurick scale improved; however, the functional outcome indicated by the JOACMEQ-LEF score did not. The mJOA results were consistent with the results of previous studies, in which the mJOA and Nurick scale have been demonstrated to improve 3 and 6 months after surgery in patients with CSM [42, 43]. Moreover, a previous study that used the functional independence measure for assessing locomotion in patients with CSM reported a positive surgical effect on locomotion [44].…”
Section: Discussionsupporting
confidence: 89%
“…Our literature search of cases of cervical spondylosis presenting with severe or very severe symptoms related to myelopathy revealed that although effective and the extent of improvement is substantial, the results of decompressive surgical treatment were only marginally successful, and the patients continued to have “significant” residual neurological deficits. [222324] Although exact comparison with other clinical reports on the subject is difficult or impossible to make, it appears that the results of our surgical treatment that involved only spinal stabilization were significantly superior to that obtained by surgical treatment that involved decompression of bone and soft tissue elements. In the various reported case series, the bulk of clinical improvement treated by decompressive surgery has been identified 6 months postoperatively; all our patients showed significant clinical symptomatic improvement in the “immediate” postoperative period.…”
Section: Discussionmentioning
confidence: 70%